2011
DOI: 10.7454/mst.v15i1.862
|View full text |Cite
|
Sign up to set email alerts
|

FORMATION OF CaCO3 PARTICLE AND CONDUCTIVITY OF Na2CO3 AND CaCl2 SOLUTION UNDER MAGNETIC FIELD ON DYNAMIC FLUID SYSTEM

Abstract: Hard water causes the CaCO 3 scale formation on the pipe walls and heat exchanger equipments in industrial or domestic water processes. A great number of experimental researches on the prevention of the CaCO 3 precipitation process by magnetic field have been carried out. In this research, Na 2 CO 3 and CaCl 2 solutions was magnetized in the circulated flow condition (dynamic fluid system). The velocity of fluid and the circulation time was modified to examine its influences to the magnetization process. CaCO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…us, many achievements about crystallization impacts are obtained, such as water hardness, alkalinity, saturation index, salinity, temperature, pH, hydraulic gradient, flow rate, thickness of diffusion boundary layer, and so on [7][8][9][10][11][12]. Another popular topic is that how the magnetic field influences on calcium carbonate crystallization [13][14][15][16][17][18][19]. Reis et al [20] proposed a two-fluid model of homogeneous crystallization of calcium carbonate in highly supersaturated solutions.…”
Section: Introductionmentioning
confidence: 99%
“…us, many achievements about crystallization impacts are obtained, such as water hardness, alkalinity, saturation index, salinity, temperature, pH, hydraulic gradient, flow rate, thickness of diffusion boundary layer, and so on [7][8][9][10][11][12]. Another popular topic is that how the magnetic field influences on calcium carbonate crystallization [13][14][15][16][17][18][19]. Reis et al [20] proposed a two-fluid model of homogeneous crystallization of calcium carbonate in highly supersaturated solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Man and Zhu [16] found that magnetic field could inhibit crystal formation. In addition, there were many studies on the influence of electromagnetic field on crystallization [6,[15][16][17][18][19][20]. Recent studies showed that the pulsed magnetic field is more advantageous to restrain the formation of scale than the constant magnetic field [21].…”
Section: Introductionmentioning
confidence: 99%
“…Discharges have been studied both in low-viscosity liquids, such as water 10−12 and liquefied noble gases, 12 and high-viscosity liquids, such as oil 13 and glycerin. 14 Discharge gaps may have dimensions from a few microns 15,16 or millimeters 17 to one meter. 13 In this paper electrical nanosecond microdischarges in liquid bee's honey are studied for the first time.…”
mentioning
confidence: 99%
“…Multiple technologies have been developed using discharge in liquids, such as purification and sterilization of liquids, change of color, destruction of living tissues in medicine, and so forth. Discharges have been studied both in low-viscosity liquids, such as water and liquefied noble gases, and high-viscosity liquids, such as oil and glycerin . Discharge gaps may have dimensions from a few microns , or millimeters to one meter …”
mentioning
confidence: 99%